Maritime Security and the Law of the Sea : Help or Hindrance? - Evans, Malcolm D. (Malcolm David), 1959-; Galani, Sofia (Edward Elgar Publishing Limited, 2020)
Exploring everything from contemporary challenges to ocean security this book offers detailed insights into the increasing activities of state and non-state actors at sea. Chapters revisit the United Nations Convention on the Law of the Sea (LOSC), highlighting how not all maritime security threats can be addressed by this, and further looking at the ways in which the LOSC may even hinder maritime security. Featuring contributions from both expert academics and practitioners in the field, the book explores new maritime security threats posed by non-state actors, such as piracy and illegal fishing. It analyses how states have had to reconsider their understanding of maritime security and rethink the use and protection of their maritime domain in the face of modern challenges, including the robotics revolution, the rise of unmanned systems and the blue economy agenda. Providing a comprehensive analysis of the interplay between LOSC and maritime security, this is key reading for scholars of maritime law, international relations and security studies. Practitioners working in the shipping industry or fishing sector, as well as maritime law enforcement officials will benefit from the practical advice offered.